Prevalence of obesity and dietary habits of university students: a cross-sectional study (Asian Journal of Medical and Biological Research, 2019)
The objectives of this study was to assess the prevalence of overweight and obesity in a sample of students from the Patuakhali Science and Technology University, Bangladesh and examine their usual eating habits. A cross-sectional survey of 260 students (65.38% male and 34.62% female) aged 20.81 ± 1.63 were chosen randomly from the Patuakhali Science and Technology University campus during May to July 2019. Students were asked to fill out a self-reported questionnaire that included questions on their eating, drinking and smoking habits. Also, their weight, height and body mass index were measured. Body mass index (BMI) was used to assess students' weight status. Statistical analyses were performed using the SPSS software (version 23.0). Results shows that, majority of the students (67.3%) were of normal weight. Based on BMI classification, the prevalence of overweight was more common among the male students compared to females (23.5% vs. 10%). In contrast, prevalence of obesity was more common among female students (3.3% vs. 2.9%). A significant difference in BMI was observed between male and female students (p